Application of impact-echo method for rockbolt length detection. (17th January 2022) - Lin, Yu-Feng; Ye, Jhih-Wei; Lo, Chia-Ming
Highlights: The study is the first to explore the method of correcting the stress wave velocity in the case of incomplete anchoring to deal with the problem of excessive detection errors. To design rockbolts specimens with various anchoring ratios that will be able to simulate possible defects in construction. Generally, for rock bolts anchored by grouting, the wave velocity of the anchoring layer material must be obtained first, and then the reasonable and the correct rockbolt length can be obtained by the method. Abstract: This study examines the spectral responses resulting from the use of the impact-echo method for rockbolt length detection. A rockbolt is a thin long member that is often used in tunnels or slope protection works to fasten structures and soil/rock mass tightly together. It involves embedding a long steel bolt fully anchored to the original structure to resist strong pulling forces and stabilize the original structure or serve as a connecting member between two materials. Inadequate embedment length or poor grouting can prevent rockbolts from serving the function they were designed for and result in rockbolt failure. This study employed finite element analysis to conduct numerical simulation analyses of the stress wave signals in rockbolts and then used the impact-echo method to measure rockbolt length and grout integrity. Our results indicate that the impact-echo method can be used to determine rockbolt length but requires prior knowledge of whether the rockbolt is grouted. If not, then its detection signals will be similar to those of a bare steel bar. The rockbolt length can then be calculated using the theoretical wave velocity in a steel bar and the fundamental frequency derived from measurements. If the rockbolt is grouted, then the wave velocity in the grout material must be known so that the accurate length of the rockbolt can be derived.